Sarajevo in the Procrustean bed: "Siege" of a divided city - Stanar Dragan (Srpska Politička Misao)
In this paper author aims to explain how constructed narratives condition the use of certain notions examining the (mis)use of the notion "siege" in the case of Sarajevo during the war in Bosnia and Herzegovina from 1992 to 1995. Conceptual analysis of the notion "siege" enables identification of essential features of this notion, which then in effect determine its logical scope and reach of usage. By analyzing the case of Sarajevo, the author proves that events in this city did not reflect essential features of the notion "siege." Therefore war-time Sarajevo does not fall in the logical reach of that notion, but rather of a "divided city." In conclusion, the author explains that mainstream media, academia, and many officials have been insisting on using the notion "siege." It is the only notion that fits the preconstructed narrative aiming to explain the war in Bosnia and Herzegovina.